The effects of intermittent fasting during the month of ramadan in chronic haemodialysis patients in a tropical climate country - Adnan, W.A.H.W.M.; Zaharan, N.L.; Wong, M.H.; Lim, S.K. (Public Library Science, 2014)
Background: Chronic kidney disease is an emerging problem in the majority Muslim countries. Despite the uncertainties of the risks involved, some Muslim patients undergoing chronic haemodialysis choose to observe intermittent fasting during the month of Ramadan. This study aims to investigate the effect of Ramadan fasting in haemodialysis patients residing in a tropical climate country. Methods: This prospective cross sectional study recruited Muslim patients on regular haemodialysis from three haemodialysis centres in Kuala Lumpur from 15th July 2011 to 29th August 2011. Patients who fasted for any number of days were included (n=35, 54% female, age 54 +/- 11 years). 89% of patients fasted for more than 15 days and 49% were diabetics. Dialysis parameters and blood samples were obtained one week prior to Ramadan and during the last week of Ramadan. The differences in dialysis parameters and biochemical values pre- and end-Ramadan were examined using paired t-test. Results: Both pre- and post-dialysis weight were significantly decreased during Ramadan fasting compared to the month prior (p= <0.001). There was a significant decrease in the amount of ultrafiltration (p=0.002). There were no significant differences in dry weight, inter-dialytic weight gain, mean urea reduction ratio or blood pressure measurements comparing pre- and end of Ramadan fasting. There was a significant increase in serum albumin level (p=0.006) and decrease in serum phosphate level (p=0.02) at the end of Ramadan. Conclusion: Ramadan fasting is associated with reduced weight, improved serum albumin and phosphate level in our population of haemodialysis patients. A larger multi-centre study will allow us to understand more about the effects of fasting in this population.